Curing agent, two-component adhesive, adhesive composition, cured product, laminate and method for producing same, packaging material, and package
The laminate, composed of a polyol, polyisocyanate, and epoxy compound, effectively addresses the issue of decreased adhesive strength in packaging materials under high temperature hydrothermal conditions, maintaining excellent sealing properties and adhesion.
Patent Information
- Application Number
- JP2021141153
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-06
- Filing Date
- 2021-08-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-08-03
AI Technical Summary
Packaging materials with electrostatic ink compositions face challenges in maintaining sealing properties under high temperature hydrothermal treatment conditions due to decreased adhesive strength between laminate layers.
A laminate is developed using an adhesive composition comprising a polyol, a polyisocyanate, and an epoxy compound, with specific molar ratios and content percentages to ensure high adhesion strength and flexibility, even under high temperature conditions.
The laminate maintains exceptionally high adhesion strength and sealing properties under high temperature hydrothermal treatment, preventing deterioration and ensuring the quality of packaged items.
Smart Images

Figure 0007661835000008 
Figure 0007661835000009 
Figure 0007661835000010
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a curing agent, a two-component adhesive, an adhesive composition, a cured product, a laminate and a method for producing the same, a packaging material, and a package. [Background technology]
[0002] Packaging bags for sealing and preserving packaged items such as food are known. Packages using thin films or sheets are used as packaging bags. Various information such as product, brand, manufacturer, etc. is printed on such packaging bags. As such printing means, a digital printer using an electrostatic ink composition is known.
[0003] For example, Patent Document 1 proposes applying a primer resin to a first flexible substrate such as a PET film to obtain a coated surface, performing electrostatic printing on the coated surface using a digital printer (Indigo 20000 label and packaging digital printer manufactured by HP), and applying a crosslinking composition. After performing the predetermined steps in this manner, a technology is proposed in which the first flexible substrate to which a predetermined component has been applied and a second flexible substrate are laminated to obtain a packaging material. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-530478 A Summary of the Invention [Problem to be solved by the invention]
[0005] Packaging materials are used for various purposes. For example, packaging materials for packaging retort foods may be heated, for example, under high-temperature hot water treatment conditions. In order to maintain the quality of the packaged items even under such heating conditions, it is required to maintain a high level of sealability. However, in a laminate including a printed matter of an electrostatic ink composition by a digital printer, there is a concern that the adhesive strength between the layers constituting the laminate is reduced, and the sealability of the packaged items may be impaired.
[0006] In view of this, the present disclosure provides a laminate capable of maintaining a sufficiently high adhesive strength between layers even under high-temperature hot water treatment conditions, and a method for producing the same. Also provided are a curing agent, an adhesive composition, a two-component adhesive, and a cured product that are useful for obtaining such a laminate. Also provided is a packaging material that has excellent sealing properties by including such a laminate. Also provided is a package packaged with a packaging material that has excellent sealing properties. [Means for solving the problem]
[0007] The present disclosure provides an adhesive composition for adhering a printed surface on which an electrostatic ink composition is printed, the adhesive composition containing a base agent containing a polyol, a curing agent containing a polyisocyanate, and an epoxy compound. By containing these components, the adhesive composition can adhere a printed surface on which an electrostatic ink composition is printed with high adhesive strength. In addition, the adhesive composition is considered to have an effect of agglomerating the electrostatic ink composition to improve the strength of the electrostatic ink layer. Electrostatic ink compositions usually have low heat resistance and water resistance. However, due to the above-mentioned action, the adhesive composition can maintain high adhesive strength under high-temperature hot water treatment conditions.
[0008] In the adhesive composition, the molar ratio of the epoxy groups contained in the epoxy compound to the isocyanate groups contained in the polyisocyanate may be 0.5 to 10. This makes it possible to maintain a sufficiently high adhesive strength under high-temperature hot water treatment conditions.
[0009] In the adhesive composition, the molar ratio of the isocyanate groups contained in the polyisocyanate to the hydroxyl groups contained in the polyol may be 0.5-10. This makes it possible to form a cured product that has high adhesive strength and excellent flexibility.
[0010] The adhesive composition may contain 3 to 25 parts by mass of an epoxy compound per 100 parts by mass of polyol. This allows the adhesive composition to maintain high adhesive strength while also having excellent shear suppression. Therefore, when bonding surfaces are bonded together with the adhesive composition, it is possible to suppress the surfaces from shifting from each other and the adhesive from protruding after bonding.
[0011] The adhesive composition may contain 10 to 50 parts by mass of polyisocyanate per 100 parts by mass of polyol, which can provide sufficiently high seal strength and adhesive strength under high-temperature hot water treatment conditions.
[0012] The adhesive composition may be used to bond a printed surface on which an electrostatic ink composition is printed to a substrate. Electrostatic ink compositions usually have low heat resistance and water resistance. However, when the printed surface is bonded using the adhesive composition, excellent adhesion can be maintained even under conditions of contact with heated water. Therefore, the adhesive strength between the bonding surfaces can be prevented from decreasing.
[0013] The polyol may be an aliphatic polyester polyol. The epoxy compound may have epoxy groups at both ends. This provides high adhesive strength not only at room temperature but also under high-temperature hot water treatment conditions.
[0014] The epoxy compound may include a bifunctional alicyclic epoxy compound. Such an epoxy compound is bifunctional, which increases the number of crosslinking points with the electrostatic ink composition and the primer resin, thereby accelerating the curing reaction of the adhesive, and facilitating curing. In addition, the epoxy compound is alicyclic, which can suppress the reaction with the polyisocyanate due to steric hindrance. Therefore, the epoxy compound can stably exert the curing function.
[0015] The polyisocyanate may contain a xylylene diisocyanate derivative. The content of the xylylene diisocyanate derivative in the entire polyisocyanate may be 10% by mass or more. This can increase the reactivity with polyols and improve curability.
[0016] The adhesive composition may have a glass transition temperature of 20° C. or lower as determined by dynamic viscoelasticity measurement after curing. Such an adhesive composition has excellent flexibility after curing, and therefore can reduce stress generated during lamination. Therefore, the adhesive strength can be further increased.
[0017] The present disclosure provides a curing agent for an adhesive for adhering a printed surface on which an electrostatic ink composition is printed, the curing agent containing a polyisocyanate and an epoxy compound, in which the molar ratio of the epoxy group contained in the epoxy compound to the isocyanate group contained in the polyisocyanate is 0.5 to 10. This curing agent has excellent stability in liquid, and can therefore maintain the curing function of the polyisocyanate at a high level. Therefore, even under high-temperature hot water treatment conditions, the curing agent can adhere the printed surface on which the electrostatic ink composition is printed with sufficiently high strength.
[0018] The epoxy compound in the curing agent may include a bifunctional alicyclic epoxy compound. Such an epoxy compound is alicyclic, and thus can suppress the reaction with polyisocyanate due to steric hindrance. Therefore, the quality of the curing agent can be stably maintained. And, being bifunctional, it can increase the crosslinking points with the electrostatic ink composition and the primer resin, promote the curing reaction of the adhesive, and make it easier to cure.
[0019] The polyisocyanate in the curing agent may contain a xylylene diisocyanate derivative. The content of the xylylene diisocyanate derivative in the entire polyisocyanate may be 10% by mass or more. This can increase the reactivity with the base agent and improve the curability.
[0020] The present disclosure provides a two-liquid adhesive for adhering a printed surface on which an electrostatic ink composition is printed, the two-liquid adhesive having a first liquid containing a base agent and a second liquid containing any of the above-mentioned curing agents. Such a two-liquid adhesive can suppress the reaction of polyisocyanate and sufficiently maintain its function as an adhesive. Therefore, the adhesive strength rises well when the first liquid and the second liquid are mixed. And, when the first liquid and the second liquid are mixed to form an adhesive composition, the above-mentioned adhesive composition is applied on the electrostatic ink composition, and cured, it is considered that the adhesive composition has an effect of aggregating the electrostatic ink composition and improving the strength of the ink itself. Therefore, even under high-temperature hot water treatment conditions, the printed surface on which the electrostatic ink composition is printed can be adhered with sufficiently high strength.
[0021] The base agent in the two-component adhesive may contain a polyol. The polyol reacts smoothly with the polyisocyanate to cure. Since the curing agent contains an epoxy compound, the electrostatic ink composition can be cured and the printed surface on which the electrostatic ink composition is printed can be bonded with sufficiently high adhesive strength under high-temperature hot water treatment conditions.
[0022] The molar ratio of the isocyanate groups contained in the polyisocyanate contained in the curing agent to the hydroxyl groups contained in the polyol contained in the base agent may be 0.5 to 10. This makes it possible to form a cured product that has high adhesive strength and excellent flexibility.
[0023] The polyol contained in the base agent may be an aliphatic polyester polyol. The epoxy compound contained in the curing agent may have epoxy groups at both ends. This makes it possible to obtain an adhesive having high adhesive strength not only at room temperature but also under high-temperature hot water treatment conditions.
[0024] The present disclosure provides a cured product obtained by curing any one of the adhesive compositions described above. Such a cured product adheres to a printed surface on which an electrostatic ink composition is printed with a sufficiently high adhesive strength even under high-temperature hot water treatment conditions.
[0025] The glass transition temperature of the cured product determined by dynamic viscoelasticity measurement may be 20° C. or lower. Such a cured product has excellent flexibility, and therefore can relieve stress caused by adhesion. Therefore, the adhesive strength can be further increased.
[0026] The present disclosure provides a laminate comprising a first substrate, an adhesive layer, and a second substrate in this order, the laminate having an electrostatic ink layer composed of an electrostatic ink composition between at least one of the first substrate and the second substrate and the adhesive layer, the adhesive layer including one or both of a polyurethane and an epoxy compound, and a crosslinked product thereof.
[0027] The electrostatic ink composition and the electrostatic ink layer formed therefrom usually have low heat resistance and water resistance. However, the laminate includes an adhesive layer containing polyurethane and an epoxy compound. Such an adhesive layer is considered to have excellent adhesion to the electrostatic ink layer and to have the effect of agglomerating the electrostatic ink composition to improve the strength of the electrostatic ink layer. Therefore, even under high-temperature hot water treatment conditions, the adhesive strength between the layers of the laminate can be maintained sufficiently high. In addition, such a laminate can be manufactured with high productivity because it does not require a separate coating layer of an epoxy compound.
[0028] The present disclosure provides a laminate comprising a first substrate, an adhesive layer, and a second substrate in this order, the laminate having an electrostatic ink layer composed of an electrostatic ink composition between at least one of the first substrate or the second substrate and the adhesive layer, the adhesive layer including a polymer of a polyol, a polyisocyanate, and an epoxy compound.
[0029] The laminate includes an adhesive layer containing a polymer of a polyol, a polyisocyanate, and an epoxy compound. It is believed that such an adhesive layer has excellent adhesion to the electrostatic ink layer and has the effect of agglomerating the electrostatic ink composition to improve the strength of the electrostatic ink layer. Therefore, even under high-temperature hot water treatment conditions, the adhesive strength between the layers of the laminate can be maintained sufficiently high. In addition, since such a laminate does not require a separate coating layer of an epoxy compound, it can be manufactured with high productivity.
[0030] The laminate may have a primer layer between the first substrate and the electrostatic ink layer. By having the primer layer, printing with a digital printer can be made easier.
[0031] The present disclosure provides a packaging material comprising any one of the laminates described above. Since the packaging material comprises the laminate described above, the packaging material can sufficiently maintain excellent sealing of the packaged item even when used in applications where the packaged item is exposed to high-temperature hot water treatment conditions. Therefore, the packaging material can be used in a variety of applications.
[0032] The present disclosure provides a package including the packaging material and an item to be packaged in the packaging material. Since the package is packaged in the packaging material, the quality of the item can be sufficiently maintained.
[0033] The present disclosure provides a method for producing a laminate, comprising the steps of printing an electrostatic ink composition on one side of a first substrate to obtain a printed surface, and adhering the printed surface to one side of a second substrate using any of the adhesive compositions described above. In this method, the printed surface obtained by printing the electrostatic ink composition is adhered to one side of the second substrate using an adhesive composition. Therefore, the printed surface can be adhered with high adhesive strength. In addition, the adhesive composition is considered to have the effect of agglomerating the electrostatic ink composition to improve the strength of the ink itself. Therefore, a laminate having high adhesive strength can be obtained under high-temperature hot water treatment conditions. In addition, such a laminate can be produced with high productivity because it does not require a separate coating layer of an epoxy compound.
[0034] The present disclosure provides a method for producing a laminate, comprising the steps of: printing an electrostatic ink composition on one side of a first substrate to obtain a printed surface; mixing the first and second liquids of any of the above-mentioned two-liquid adhesives to prepare an adhesive composition; and bonding the printed surface and one side of a second substrate using the adhesive composition. In this method, the printed surface obtained by printing the electrostatic ink composition is bonded to one side of the second substrate using an adhesive composition prepared by mixing the first and second liquids. Therefore, the printed surface can be bonded with high adhesive strength. In addition, the adhesive composition is considered to have an effect of agglomerating the electrostatic ink composition to improve the strength of the ink itself. Therefore, a laminate having high adhesive strength under high-temperature hot water treatment conditions can be obtained. In addition, such a laminate can be produced with high productivity because it is not necessary to provide a separate coating layer of an epoxy compound. In addition, since a two-liquid adhesive having a first and second liquid is used, the workability during bonding can be improved. In addition, the occurrence of poor blending during preparation of the adhesive composition can be suppressed, and the variation in adhesive strength can be sufficiently reduced. Effect of the Invention
[0035] According to the present disclosure, it is possible to provide a laminate capable of maintaining a sufficiently high adhesive strength between layers even under high-temperature hot water treatment conditions, and a method for producing the same. It is also possible to provide a curing agent, an adhesive composition, a two-component adhesive, and a cured product that are useful for obtaining such a laminate. It is also possible to provide a packaging material having excellent sealing properties by using such a laminate. It is also possible to provide a package packaged with a packaging material having excellent sealing properties. [Brief description of the drawings]
[0036] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of a laminate. [Diagram 2] FIG. 2 is a plan view showing an example of a packaging bag and a packaging body. [Diagram 3] FIG. 11 is a plan view showing another example of a packaging bag. [Figure 4]3 is a graph showing the change over time in the NCO reaction rate of an adhesive composition. [Diagram 5] 1 is a graph showing the change over time in adhesive strength of an adhesive composition. [Figure 6] 1 is a graph showing the change over time in pot life of an adhesive composition. [Figure 7] 1 is a graph showing the results of dynamic viscoelasticity measurement of a cured product obtained by curing the adhesive composition of Example 7. [Figure 8] 2 is a graph showing the results of dynamic viscoelasticity measurement of a cured product obtained by curing the adhesive composition of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] The embodiments of the present disclosure will be described below with reference to the drawings as needed. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents. In the description, the same elements or elements having the same functions are designated by the same reference numerals, and redundant descriptions are omitted as the case may be. Furthermore, positional relationships such as up, down, left, and right are based on the positional relationships shown in the drawings, unless otherwise specified. Furthermore, the dimensional ratios of the drawings are not limited to those shown in the drawings.
[0038] The adhesive composition according to one embodiment contains a polyol, a polyisocyanate, and an epoxy compound. The polyol has, for example, a number average molecular weight of 400 or more and has two or more hydroxyl groups in one molecule. The polyisocyanate has two or more isocyanate groups in one molecule. The polyol and the polyisocyanate react as a base agent and a curing agent, respectively, to produce polyurethane (polyurethane adhesive). The polyol may have a number average molecular weight of, for example, 10,000 or less.
[0039] The polyol may contain at least one selected from the group consisting of polyester polyols and polyether polyols. Among these, from the viewpoint of sufficiently increasing the adhesive strength, the polyol may contain a polyester polyol or may contain an aliphatic polyester polyol.
[0040] The polyester polyol can be obtained, for example, by a condensation reaction or an ester exchange reaction between a polyhydric alcohol and a polybasic acid, its alkyl ester, its acid anhydride, or its acid halide. Examples of the polyhydric alcohol include a low molecular weight diol, a low molecular weight triol, and a low molecular weight polyol having four or more hydroxyl groups.
[0041] Examples of low molecular weight diols include ethylene glycol, propylene glycol, trimethylene glycol, 1,4-butylene glycol, 1,3-butylene glycol, 1,2-butylene glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol, neopentyl glycol, 1,6-hexanediol, 2,2-diethyl-1,3-propanediol, 3,3-dimethylolheptane, and 2-ethyl-2-butyl-1,3-propanediol.
[0042] Examples of low molecular weight triols include glycerin, 2-methyl-2-hydroxymethyl-1,3-propanediol, 2,4-dihydroxy-3-hydroxymethylpentane, 1,2,6-hexanetriol, trimethylolethane, trimethylolpropane, 2-methyl-2-hydroxymethyl-1,3-propanediol, 2,4-dihydroxy-3-(hydroxymethyl)pentane, and 2,2-bis(hydroxymethyl)-3-butanol.
[0043] Examples of low molecular weight polyols having four or more hydroxyl groups include tetramethylolmethane, pentaerythritol, dipentaerythritol, D-sorbitol, xylitol, D-mannitol, and D-mannite.
[0044] Examples of the alkyl ester of a polybasic acid include methyl ester and ethyl ester of a polybasic acid. Examples of the acid anhydride include acid anhydrides derived from a polybasic acid. For example, oxalic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, 2-alkyl (C12-18) succinic anhydride, tetrahydrophthalic anhydride, and trimellitic anhydride can be mentioned.
[0045] The acid halide may be an acid halide derived from the above-mentioned polybasic acid, such as oxalic acid dichloride, adipic acid dichloride, or sebacic acid dichloride.
[0046] The polyether polyol may be a polyalkylene oxide. For example, it may be obtained by addition reaction of an alkylene oxide such as ethylene oxide and / or propylene oxide with a low molecular weight polyol as an initiator. Specific examples include polyethylene glycol, polypropylene glycol, and polyethylene polypropylene glycol (random or block copolymer). In addition, for example, polytetramethylene ether glycol obtained by ring-opening polymerization of tetrahydrofuran may be mentioned.
[0047] Examples of polyisocyanates include polyisocyanate monomers, polyisocyanate derivatives, and isocyanate-terminated prepolymers. The adhesive composition may contain a plurality of different polyisocyanates. The molar ratio (NCO / OH) of the isocyanate groups contained in the polyisocyanate to the hydroxyl groups of the polyol may be 0.5 to 10. Such an adhesive composition can form a cured product having high adhesive strength and excellent flexibility.
[0048] Examples of the polyisocyanate monomer include aliphatic polyisocyanates, aromatic polyisocyanates, araliphatic polyisocyanates, and alicyclic polyisocyanates.
[0049] Examples of aliphatic polyisocyanates include trimethylene diisocyanate, 1,2-propylene diisocyanate, butylene diisocyanate (tetramethylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate), 1,5-pentamethylene diisocyanate (PDI), hexamethylene diisocyanate (HDI), 2,4,4-trimethylhexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and 2,6-diisocyanate methylcaprate.
[0050] Examples of the aromatic aliphatic polyisocyanate include xylylene diisocyanate derivatives, such as xylylene diisocyanate (1,3-xylylene diisocyanate or 1,4-xylylene diisocyanate) (XDI), tetramethyl xylylene diisocyanate (1,3-tetramethyl xylylene diisocyanate or 1,4-tetramethyl xylylene diisocyanate) (TMXDI), ω,ω'-diisocyanate-1,4-diethylbenzene, and a polyol modified product of xylylene diisocyanate obtained by reacting xylylene diisocyanate with trimethylolpropane.
[0051] The content of the xylylene diisocyanate derivative relative to the entire polyisocyanate may be 10% by mass or more, 20% by mass or more, 30% by mass or more, or 40% by mass or more from the viewpoint of improving the reactivity with the base agent (e.g., polyol). By making it 30% by mass or more, the reactivity can be further increased.
[0052] Examples of alicyclic polyisocyanates include 1,3-cyclopentane diisocyanate, 1,3-cyclopentene diisocyanate, cyclohexane diisocyanate (1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate), 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (isophorodiisocyanate) (IPDI), methylcyclohexane diisocyanate (methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate), and norbornane diisocyanate (NBDI).
[0053] Examples of the polyisocyanate derivatives include polymers of the above-mentioned polyisocyanate monomers, allophanate-modified products, polyol-modified products, polyol-modified products produced by the reaction of a monomer with an alcohol, biuret-modified products, urea-modified products, oxadiazinetrione-modified products, carbodiimide-modified products, uretdione-modified products, and uretonimine-modified products.
[0054] The isocyanate-terminated prepolymer is a urethane prepolymer having at least two isocyanate groups at the molecular end. It can be obtained by a urethane reaction between at least one selected from the group consisting of polyisocyanate monomers, polyisocyanate derivatives, and isocyanate-terminated prepolymers, and a polyol. In this case, the molar ratio (NCO / OH) of the isocyanate groups contained in the polyisocyanate to the hydroxyl groups of the polyol may be 0.5 or more, 0.6 or more, 0.8 or more, 1 or more, or 1.5 or more. The molar ratio (NCO / OH) may be 10 or less, 5 or less, 4 or less, or 3 or less. Examples of the numerical range of the molar ratio (NCO / OH) include 0.5 to 10, 0.5 to 5, 0.8 to 4, and 0.6 to 3.
[0055] The epoxy compound may be a compound having one or more epoxy groups in one molecule, and may be a compound having epoxy groups at least at both ends. Examples of the epoxy compound include glycidyl ether type epoxy compounds, glycidyl amine type epoxy compounds, glycidyl ester type epoxy compounds, and alicyclic epoxy compounds (alicyclic epoxy compounds).
[0056] The molecular weight of the epoxy compound may be 500 or less, 450 or less, or 400 or less. Such an epoxy compound can be sufficiently permeated into the electrostatic ink composition constituting the electrostatic ink layer. The lower limit of the molecular weight of the epoxy compound may be, for example, 98.
[0057] Examples of alicyclic epoxy compounds include epoxycyclohexylmethyl-epoxycyclohexanecarboxylate and bis(epoxycyclohexyl)adipate.
[0058] Examples of monofunctional alicyclic epoxy compounds having one epoxy group per molecule include 3,4-epoxycyclohexylmethyl methacrylate and 1,2-epoxy-4-vinylcyclohexane. Examples of bifunctional epoxy compounds having two epoxy groups per molecule include 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, bis(3,4-epoxycyclohexylmethyl)adipate, and 4-vinylcyclohexene dioxide. Examples of epoxy compounds having one or more epoxy groups per molecule include 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol represented by the following general formula (I).
[0059] [ka]
[0060] In the above general formula (I), n may be an integer of 1-4.
[0061] The epoxy compound preferably contains a bifunctional alicyclic epoxy compound. By being bifunctional, the number of crosslinking points with the electrostatic ink composition and the primer resin can be increased, accelerating the curing reaction of the adhesive and making it easier to cure. In addition, by being alicyclic, the reaction with the polyisocyanate can be suppressed due to steric hindrance. Therefore, the curing function can be stably exhibited.
[0062] In the adhesive composition, the content of the epoxy compound relative to 100 parts by mass of polyol may be 3 to 25 parts by mass, 6 to 25 parts by mass, or 8 to 20 parts by mass, from the viewpoint of achieving both high adhesive strength and excellent shear suppression. If the content of the epoxy compound is too high, the excellent shear suppression tends to be impaired. That is, when an adhesive layer is formed, the adhesive surfaces may be misaligned or the adhesive composition may protrude. If the amount of the epoxy compound is too small, the adhesive strength tends to decrease, especially under high-temperature hot water treatment conditions.
[0063] In the adhesive composition, the content of polyisocyanate per 100 parts by mass of polyol may be 10 to 50 parts by mass, 15 to 35 parts by mass, or 20 to 30 parts by mass, from the viewpoint of sufficiently increasing the seal strength and the adhesive strength under high-temperature hot water treatment conditions.
[0064] The molar ratio of the epoxy groups contained in the epoxy compound to the isocyanate groups contained in the polyisocyanate may be 0.5 to 10, 1.5 to 9, or 2.0 to 6.5. This makes it possible to maintain a sufficiently high adhesive strength under high-temperature hot water treatment conditions.
[0065] In addition to the above-mentioned components, the adhesive composition may contain optional components such as additives. Examples of additives include antioxidants, ultraviolet absorbers, light stabilizers, fillers, silane coupling agents, epoxy resins, catalysts, coating property improvers, leveling agents, nucleating agents, lubricants, release agents, defoamers, plasticizers, surfactants, pigments, dyes, organic fine particles, inorganic fine particles, antifungal agents, and flame retardants. In addition, the adhesive composition may contain urethane catalysts such as organic acid-based, tin-based, lead-based, and amine-based. The adhesive composition may contain a solvent such as an organic solvent.
[0066] The adhesive composition can be used as an adhesive for bonding a printed surface, on which an electrostatic ink composition is printed, to a substrate. The adhesive composition forms a urethane bond by a reaction between a polyol and a polyisocyanate, and functions as an adhesive. Even in the presence of an epoxy compound, the formation of the urethane bond proceeds smoothly, so that the printed surface and the substrate can be bonded with sufficiently high adhesive strength.
[0067] The adhesive composition may have a function of crosslinking the electrostatic ink composition as well as forming a urethane bond. This can improve the adhesive strength between the printed surface and the substrate. Even if the ink coverage rate on the printed surface is increased, the epoxy compound can be sufficiently permeated into the electrostatic ink layer formed by the electrostatic ink composition by increasing the content of the epoxy compound contained in the adhesive composition accordingly. The permeated epoxy compound has the effect of crosslinking the electrostatic ink composition, thereby increasing the strength of the electrostatic ink composition (electrostatic ink layer). Therefore, even if the ink coverage rate on the printed surface is increased, the adhesive strength can be maintained high after heat treatment under retort conditions of 110 to 135°C.
[0068] The adhesive composition can maintain high adhesive strength even after heat treatment, while also having an excellent pot life. Therefore, the adhesive composition is excellent in workability such as coating and lamination when adhering the printed surface and the substrate. The adhesive composition contains polyol and polyisocyanate that form urethane, and an epoxy compound, which are cured to form an adhesive layer. This can reduce the number of layers that constitute the laminate, compared to the case where an adhesive layer containing only polyurethane and an epoxy coating layer are separately provided. Therefore, for example, when producing a laminate by roll-to-roll, problems such as roll meandering after aging and wrinkles due to blocking do not occur. In addition, the aging process after coating can be reduced, and the efficiency of production can be improved.
[0069] In a laminate in which the electrostatic ink layer on the printed surface is in direct contact with the adhesive composition, the components such as epoxy compound and / or polyisocyanate contained in the adhesive composition sufficiently penetrate into the electrostatic ink layer. This crosslinks the electrostatic ink composition constituting the electrostatic ink layer, and improves the adhesive strength of the laminate. In addition, even if the printed surface includes a plain area (transparent area) without the electrostatic ink layer composed of the electrostatic ink composition, the epoxy compound is contained in the adhesive layer, so that stickiness can be eliminated. On the other hand, if an epoxy coating layer is provided separately from the adhesive layer, when the printed surface includes a plain area, the epoxy compound becomes excessive near the plain area, and stickiness is likely to occur. In this way, the adhesive composition of the present embodiment can eliminate stickiness while adhering the printed surface including the plain area where the electrostatic ink layer is not formed with high adhesive strength.
[0070] A two-component adhesive according to one embodiment bonds a printed surface on which an electrostatic ink composition is printed to a substrate. The two-component adhesive has a first liquid containing a base material and a second liquid containing a curing agent. The two-component adhesive may be composed of only the first liquid and the second liquid. The first liquid and the second liquid exist separately and are not mixed. For example, the first liquid may be contained in a first container, and the second liquid may be contained in a second container. For example, the two-component adhesive may include a first container containing a first liquid containing a base material and a second container containing a second liquid containing a curing agent.
[0071] The base agent contained in the first liquid may contain the polyol. The curing agent contained in the second liquid may contain the polyisocyanate and the epoxy compound. The adhesive composition described above can be obtained by mixing the first liquid and the second liquid. Therefore, the description of the adhesive composition described above also applies to the two-liquid adhesive. The two-liquid adhesive has the same action and effect as the adhesive composition.
[0072] For example, the two-liquid adhesive may be prepared by mixing the first and second liquids to prepare an adhesive composition, and then bonding the printed surface and the substrate. In this way, the two-liquid adhesive is easier to mix than the three-liquid adhesive, and therefore has excellent workability. In addition, since it has excellent stability, it is suitable for industrial-scale production. Furthermore, since the adhesive composition can be obtained by simply mixing the two liquids, the variation in adhesive strength caused by poor mixing or the like can be sufficiently reduced. In addition, since the curing agent has excellent stability, the reaction activity of the polyisocyanate can be maintained at a high level. Therefore, even under high-temperature hot water treatment conditions, the printed surface on which the electrostatic ink composition is printed can be bonded with sufficiently high strength.
[0073] The curing agent according to one embodiment is used in an adhesive for bonding a printed surface, on which an electrostatic ink composition is printed, to a substrate. The curing agent contains the polyisocyanate and the epoxy compound contained in the adhesive composition. Therefore, the above description of the adhesive composition also applies to this curing agent.
[0074] The polyisocyanate and the epoxy compound contained in the curing agent are inhibited from reacting with each other. Therefore, even if the curing agent is stored in a liquid state for a long period of time, the curing function of the polyisocyanate can be maintained at a high level. Therefore, it can be suitably used as a material for a two-liquid adhesive. The adhesive composition prepared using such a curing agent can bond the printed surface on which the electrostatic ink composition is printed and the substrate with sufficiently high strength even under high-temperature hot water treatment conditions.
[0075] The cured product according to one embodiment is obtained by curing the adhesive composition described above. This cured product may constitute an adhesive layer that bonds a printing surface on which the electrostatic ink composition is printed to a substrate. The cured product may contain one or both of a polyurethane and an epoxy compound, and a crosslinked product thereof. The polyurethane may be a reaction product of the polyol and polyisocyanate described above.
[0076] The glass transition temperature of the cured product determined by dynamic viscoelasticity measurement may be 20°C or lower, or may be 15°C or lower. Such a low glass transition temperature improves flexibility at room temperature. This allows, for example, the stress generated when bonding a printed surface to a substrate to be sufficiently alleviated. This allows the adhesive strength to be further increased. From the viewpoint of improving heat resistance, the glass transition temperature may be 5°C or higher, or may be 10°C or higher. The cured product for which the glass transition temperature is measured is obtained by heating the adhesive composition at 60°C.
[0077] The laminate according to one embodiment includes a first substrate, an adhesive layer, and a second substrate in this order. The first substrate and the second substrate are bonded together by the adhesive layer. One or both of the first substrate and the second substrate may or may not be in direct contact with the adhesive layer. An optional layer may be present between one or both of the first substrate and the second substrate and the adhesive layer. An electrostatic ink composition is printed on the adhesive surface between the first substrate side and / or the second substrate side and the adhesive layer.
[0078] Electrostatic ink compositions are ink compositions used in liquid electrophotographic printing, i.e. electrostatic printing, on substrates such as paper and plastic. Electrostatic ink compositions may include colorants or pigments, such as dyes, and resins. In addition to these, they may also include a carrier fluid or liquid. They may also include charge directors, charge adjuvants, surfactants, viscosity modifiers, emulsifiers, and other additives.
[0079] The colorants include, for example, cyan pigments, magenta pigments, yellow pigments, and black pigments.The resins include thermoplastic resins such as ethylene acrylic acid copolymers, propylene acrylic acid copolymers, ethylene methacrylic acid copolymers, propylene methacrylic acid copolymers, and ethylene vinyl acetate copolymers.
[0080] Carrier liquids include hydrocarbons, silicone oils, vegetable oils, and the like. Hydrocarbons include aliphatic hydrocarbons, branched chain aliphatic hydrocarbons, and aromatic hydrocarbons. The electrostatic ink composition may be substantially free of carrier liquid when printed onto a print substrate, such as a first substrate. The carrier liquid may be removed, for example, by an electrophoretic process or evaporation during printing, thereby transferring substantially only solids to the print substrate.
[0081] Charge directors serve to maintain a sufficient electrostatic charge on the particles contained in the electrostatic ink composition and include, for example, ionic compounds such as metal salts of fatty acids, metal salts of sulfosuccinates, metal salts of oxyphosphates, metal salts of alkylbenzenesulfonic acids, metal salts of aromatic carboxylic or aromatic sulfonic acids, as well as zwitterionic and non-ionic compounds such as polyoxyethylenated alkylamines, lecithin, polyvinylpyrrolidone, and organic acid esters of polyhydric alcohols.
[0082] The charge adjuvant has the effect of increasing or stabilizing the charge of particles contained in the electrostatic ink composition. Examples of the charge adjuvant include barium petronate, calcium petronate, naphthenic acid Co salt, naphthenic acid Ca salt, naphthenic acid Cu salt, naphthenic acid Mn salt, naphthenic acid Ni salt, naphthenic acid Zn salt, naphthenic acid Fe salt, stearate Ba salt, stearate Co salt, stearate Pb salt, stearate Zn salt, stearate Al salt, stearate Cu salt, stearate Fe salt, and metal carboxylates.
[0083] The adhesive layer is formed by heating and curing the above-mentioned adhesive composition. The adhesive composition may be a so-called two-liquid curing adhesive, in which polyol is the main agent and polyisocyanate is the curing agent. Therefore, the adhesive layer may contain a polyurethane resin produced by the reaction of polyol with polyisocyanate, and an epoxy compound. The adhesive layer may also contain a polymer (crosslinked product) produced by the reaction of polyol with polyisocyanate and an epoxy compound. Such an adhesive layer has high adhesive strength even under high-temperature hot water treatment conditions. In addition, it can maintain high adhesive strength even when in contact with hot water.
[0084] The adhesive layer can be formed, for example, by applying an adhesive composition onto the electrostatic ink composition, laminating the surface onto which the adhesive composition is applied to the surface of another substrate, and curing the composition at room temperature or under heating. The amount of the adhesive composition applied is, for example, 1 to 10 g / m. 2 and may be 2 to 6 g / m 2 and may be 3 to 5 g / m 2 may be also possible.
[0085] Fig. 1 is a cross-sectional view showing a schematic example of a laminate. Fig. 1 shows a cross section along the thickness direction of the laminate. The laminate 300 has a first substrate 10, a primer layer 40, an adhesive layer 30 (adhesive composition or a cured product thereof), and a second substrate 20, in this order. The primer layer 40 is provided on one surface of the first substrate 10 on the second substrate 20 side.
[0086] At least one of the first substrate 10 and the second substrate 20 may be a flexible substrate. The flexible substrate may include, for example, one or both of a metal foil such as an aluminum foil and a thermoplastic polymer in a film form. Examples of the flexible substrate include films of biaxially oriented polypropylene (BOPP), polyethylene terephthalate (PET), oriented polyamide (OPA), non-oriented polypropylene (CPP), linear low density polyethylene (LLDPE), and low density polyethylene (LDPE). The flexible substrate may also be a deposition film in which aluminum or aluminum oxide is deposited on a PET film, or a transparent deposition film. The materials of the first substrate 10 and the second substrate 20 may be the same or different. The thickness of the first substrate 10 and the second substrate 20 may be 7 to 150 μm, 15 to 90 μm, or 20 to 80 μm.
[0087] The primer layer 40 may contain a resin. Examples of the resin include polyvinyl alcohol resin, cellulose-based resin, polyester, polyamine, polyethyleneimine resin, polyamide resin, polyurethane, polyacrylic polymer, hydroxyl-containing resin, carboxyl-containing resin, and amine-based polymer. By having the primer layer 40, printing with the electrostatic ink composition can be performed smoothly. The application amount of the resin constituting the primer layer 40 is, for example, 0.01 to 1.5 g / m. 2 and may be 0.05 to 1.0 g / m 2 may be also possible.
[0088] The electrostatic ink composition 50 is printed on the primer layer 40 by electrostatic printing using a digital printer to form an electrostatic ink layer. The electrostatic ink compositions 50 shown in FIG. 1 may have the same composition, or may have different compositions and therefore different colors. The electrostatic ink composition 50 may be crosslinked by the adhesive composition and / or the components contained in the primer layer 40. This can further increase the adhesive strength between the first substrate 10 and the second substrate 20.
[0089] The laminate 300 does not have an epoxy coating layer. In this way, since there is no need to provide an epoxy coating layer, the number of steps can be reduced accordingly, and productivity can be improved.
[0090] In this example, the adhesive layer 30 and the primer layer 40 are in direct contact between the electrostatic ink compositions 50 adjacent to each other along a direction perpendicular to the direction in which the first substrate 10 and the second substrate 20 face each other. This allows the laminate 300 to have a transparent portion (plain portion) when viewed from the direction in which the first substrate 10 and the second substrate 20 face each other. Therefore, when the laminate 300 is used as a packaging film, the packaged item can be visually recognized through the laminate 300. Even if such a transparent portion is provided, the stickiness of the adhesive layer 30 can be sufficiently suppressed by the lamination method.
[0091] In another example, adjacent electrostatic ink compositions 50 may be in contact with each other along a direction perpendicular to the direction in which the first substrate 10 and the second substrate 20 face each other. That is, it is sufficient that at least one of the adhesive surfaces that adheres to the adhesive layer 30 has the electrostatic ink composition 50 or that the adhesive surface is composed of the electrostatic ink composition 50. Since the adhesive layer 30 adheres firmly to the electrostatic ink composition 50, the first substrate 10 and the second substrate 20 can be adhered sufficiently firmly.
[0092] In yet another example, the primer layer 40 may not be present, or the primer layer 40 may be present on each of the opposing surfaces of the first substrate 10 and the second substrate 20. In addition, from the viewpoint of improving the gas barrier property and water vapor barrier property of the laminate 300, at least one of a metal layer such as an aluminum foil and a resin layer such as a nylon film may be present between the first substrate 10 and the primer layer 40 and / or between the second substrate 20 and the adhesive layer 30.
[0093] The laminate 300 is useful, for example, as a packaging material for food. The laminate 300 has excellent adhesive strength under high-temperature hot water treatment conditions and in a contact environment with hot water, and therefore can be suitably used as a packaging material for retort, a packaging material for microwave ovens, and a packaging material for boiling. The thickness of the laminate 300 may be, for example, 15 to 200 μm, or 18 to 120 μm.
[0094] A manufacturing method of the laminate 300 according to one embodiment includes the steps of forming a primer layer 40 on one side of a first substrate 10, printing an electrostatic ink composition 50 on the primer layer 40 to obtain a printed surface, and adhering the printed surface to one side of a second substrate 20 using an adhesive composition.
[0095] The primer layer 40 may be formed on one surface of the first substrate 10 by gravure printing. The primer layer 40 may be formed by crosslinking a resin raw material with a crosslinking agent. Crosslinking may be performed by irradiation with ultraviolet light, heat, ionizing radiation such as an electron beam, or non-ionizing radiation such as microwave radiation. The electrostatic ink composition 50 may be printed by electrostatic printing using a digital printer.
[0096] The adhesion between the printed surface and one side of the second substrate 20 with the adhesive composition can be performed by lamination. The lamination can be performed using any device. The epoxy compound and / or polyisocyanate contained in the adhesive composition may penetrate into the electrostatic ink composition 50 and the primer layer 40 that constitute the electrostatic ink layer, and may crosslink with the components contained in the electrostatic ink composition 50 and the primer layer 40. This makes it possible to obtain a laminate 300 in which the interfaces of the layers are sufficiently bonded.
[0097] Prior to the step of bonding using the adhesive composition, a step of preparing the adhesive composition by mixing the first liquid and the second liquid constituting the above-mentioned two-liquid adhesive may be included. By using such a two-liquid adhesive, the preparation of the adhesive composition and the bonding operation can be smoothly performed. In addition, since the variation in the mixed state of the adhesive composition is reduced, the reliability of the laminate 300 can be improved.
[0098] FIG. 2 is a plan view showing one embodiment of a packaging bag formed using the above-mentioned laminate. The packaging bag 100 is formed by bonding a pair of packaging materials 60, 62 together. The above-mentioned laminate 300 can be used as the packaging materials 60, 62. That is, the packaging bag 100 includes a sealed portion 101 formed by bonding the peripheries of a pair of film-like, substantially rectangular packaging materials 60, 62 together, and a storage portion 102 formed between the pair of packaging materials 60, 62 by the sealed portion 101. That is, the side end portion, lower end portion, and upper end portion of the packaging bag 100 are sealed by the sealed portion 101. The packaging bag 100 includes a storage portion 102 in which a packaged item (e.g., food) is stored in a non-sealed portion (sheet portion) surrounded by the sealed portion 101. The sealed portion 101 at the lower end portion may be sealed after the packaged item is filled in the storage portion 102.
[0099] The packaging materials 60, 62 may have a sealant layer on the surface of the laminate 300 and the first base material 10 or the second base material 20 of the laminate 300. In this case, the pair of packaging materials 60, 62 are overlapped so that the sealant layers face each other. The pair of film-like packaging materials 60, 62 may be bonded by an adhesive at the seal portion 101. Either the first base material 10 or the second base material 20 of the laminate 300 constituting the packaging materials 60, 62 may be on the inside.
[0100] It is not essential that the pair of packaging materials 60, 62 constituting the packaging bag 100 have the same layer structure, and for example, the pair of packaging materials 60, 62 may be composed of laminates having different layer structures.
[0101] The packaging bag 100 may be equipped with an opening means 120. The opening means has a pair of easy-to-open processed parts 124 consisting of V-shaped notches formed in the sealed part 101 at the side end, and a half-cut line 121 that serves as a slitting path between the pair of easy-to-open processed parts 124. The half-cut line 121 can be formed using a laser. The easy-to-open processed parts 124 are not limited to V-shaped notches, and may be U-shaped or I-shaped notches, or may be a group of scars.
[0102] The procedure for manufacturing the packaging bag 100 using the packaging materials 60, 62 will be described below. The laminate 300 is cut into a predetermined shape to obtain a pair of packaging materials 60, 62. The sealant layers provided on one side of the packaging materials 60, 62 are placed opposite each other and bonded together. This forms sealed portions 101 at the upper end and side ends, and forms a non-sealed portion surrounded by the sealed portions 101 in a U-shape. In this manner, a packaging bag 110 is obtained in which only the upper end (or only the lower end) is unsealed, as shown in FIG. 3. In some embodiments, the packaging bag may not have a portion of its periphery sealed as shown in FIG. 3.
[0103] Next, the packaged item is filled from the unsealed upper end (or lower end). After that, the packaging materials 60, 62 are bonded together at the upper end (or lower end) to form a sealed portion 101 at the upper end (or lower end). In this manner, a package 200 including the packaging bag 100 and the packaged item contained therein can be manufactured.
[0104] The packaging bag 100 and the packaging body 200 are particularly suitable for use with foods that are heated in hot water or in a microwave oven, since the packaging materials 60, 62 of the packaging bag 100 and the packaging body 200 are laminates that can maintain sufficiently high adhesive strength between layers even under high-temperature hot water treatment conditions. Examples of the packaging body 200 include retort packages that are heated by boiling or in a microwave oven.
[0105] Although several embodiments have been described above, the present disclosure is not limited to the above embodiments. For example, the packaging material may be a packaging film attached to the surface of a PET bottle. The shape of the packaging bag is not limited to a four-sided bag, and may be, for example, a two-sided bag, a three-sided bag, a palm-shaped bag, or a standing pouch. The laminate may include one or more optional layers in addition to the first substrate, the primer layer, the electrostatic ink layer, the adhesive layer, and the second substrate. EXAMPLES
[0106] The present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited to the following examples.
[0107] Example 1 [Preparation of adhesive composition and laminate] A polyethylene terephthalate film (PET film, thickness: 12 μm) was prepared as a first substrate. A water-based primer resin (a resin containing polyethyleneimine, manufactured by Michelman, product name: DP050) was applied to one side of the PET film to form a primer layer. The amount of water-based polyethyleneimine applied was 0.10 to 0.18 g / m 2 The coating was applied so that the result was as follows.
[0108] A predetermined printing was performed on the surface of the primer layer using a digital printer (HP Indigo 20000 label and package digital printer). The ink coverage rate from one printing was 100%. As the electrostatic ink composition, an electrostatic ink composition (HP Indigo Electroink) containing a thermoplastic resin containing a copolymer of ethylene acrylic acid and ethylene methacrylic acid was used. As the colors of the electrostatic ink composition, white (W), yellow (Y), magenta (M), and cyan (C) were used as shown in Table 1. A plurality of samples with different colors and ink coverage rates of the electrostatic ink composition were prepared. The ink coverage rates of each color and the total were as shown in Table 1. As shown in Table 1, the total ink coverage rate was 200 to 500%.
[0109] An adhesive composition having a solid content concentration of 36.5% by mass was prepared by blending an aliphatic polyester polyol (A) (manufactured by Mitsui Chemicals, Inc., product name: Takelac A626) as a main agent, a polyisocyanate (B) (manufactured by Mitsui Chemicals, Inc., product name: Takenate A50), 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate as an epoxy compound (C), and ethyl acetate as a solvent. The structure of this epoxy compound is as shown in the following formula (1). The blending ratio of each component based on mass is as shown in Table 1. The column [(B) / (A)]×100 in Table 1 shows the blending amount (parts by mass) of polyisocyanate relative to 100 parts by mass of aliphatic polyester polyol. The column [(C) / (A)]×100 in Table 1 shows the blending amount (parts by mass) of epoxy compound relative to 100 parts by mass of aliphatic polyester polyol. The column "Epoxy group / isocyanate group" in Table 1 shows the molar ratio of epoxy groups contained in the epoxy compound (C) to the isocyanate groups contained in the polyisocyanate (B).
[0110] The adhesive composition prepared as described above was applied to the printed surface of the electrostatic ink composition using a dry laminating device to form an adhesive layer. The application amount of the adhesive composition was 4.0 g / m 2 It was decided.
[0111] [ka]
[0112] As the second substrate, a substrate film having an aluminum foil (manufactured by Toyo Aluminum Co., Ltd., thickness: 7 μm), a nylon film, and a non-oriented polypropylene film in this order was prepared. Using the above-mentioned dry laminating device, the substrate film was attached to the adhesive layer so that the adhesive layer and the aluminum foil were in contact with each other, to obtain a laminate. The curing time (aging) was 40° C. for 2 days. In this manner, a laminated film (laminate) was produced.
[0113] [Measurement of adhesive strength (room temperature)] The adhesive strength of the prepared laminate was measured in accordance with JIS K 6854-1:1999. Specifically, the prepared laminate was cut into a width of 15 mm to prepare a measurement sample. After peeling between the layers at the end of the measurement sample, the peel strength between the layers of the laminate was measured using a tensile tester under conditions of an angle of 90°, a tensile speed of 300 mm / min, and room temperature. This peel strength was defined as the adhesive strength at room temperature (20°C). The measurement results are shown in Table 1.
[0114] (Examples 2 to 6) A laminate was produced and the adhesive strength was measured in the same manner as in Example 1, except that the formulation of the adhesive composition was changed as shown in Tables 1 and 2. The measurement results are shown in Tables 1 and 2.
[0115] Example 7 A two-liquid adhesive was prepared in which a first liquid consisting of an aliphatic polyester polyol (A) (manufactured by Mitsui Chemicals, Inc., product name: Takelac A626) and a second liquid consisting of a polyisocyanate (B) (manufactured by Mitsui Chemicals, Inc., product name: Takenate A50) and an epoxy compound (C) were separately contained in containers. The first liquid and the second liquid were mixed to prepare an adhesive composition having the composition shown in Table 2. A laminate was produced in the same manner as in Example 1 except that this adhesive composition was used, and the adhesive strength was measured. The measurement results are shown in Table 2.
[0116] Comparative Example 1 A laminate was produced in the same manner as in Example 1, except that the epoxy compound (C) was not added when preparing the adhesive composition, and the adhesive strength was measured. The measurement results are shown in Table 2.
[0117] Comparative Example 2 A laminate was produced in the same manner as in Example 1, except that an epoxy compound of formula (1) was applied to the printed surface on which the electrostatic ink composition was printed to provide an epoxy coating layer, and the adhesive composition of Comparative Example 1 was applied to this epoxy coating layer, and the adhesive strength was measured. The amount of the epoxy coating layer applied was an amount equivalent to 0.53 parts by mass in the composition shown in Table 2. The measurement results are shown in Table 2.
[0118] [Table 1]
[0119] [Table 2]
[0120] As shown in Tables 1 and 2, it was confirmed that the addition of an epoxy compound resulted in a higher adhesive strength than Comparative Example 1. In Comparative Example 2, a relatively high adhesive strength was obtained, but the number of steps had to be increased in order to form an epoxy coating layer in addition to the adhesive layer. It took two days to cure (age) the epoxy coating layer, reducing productivity.
[0121] In the laminate of Comparative Example 1, peeling occurred near the interface between the electrostatic ink layer and the primer layer. In the laminate of Comparative Example 2, the electrostatic ink layer underwent cohesive failure. On the other hand, in the laminates of Examples 1 to 7, peeling occurred at the interface between the electrostatic ink layer and the adhesive layer, and no cohesive failure of the electrostatic ink layer was observed. This suggests that the cohesive force of the electrostatic ink layer was improved. In Examples 1 to 7, the molar ratio of the isocyanate groups contained in the polyisocyanate (B) to the hydroxyl groups of the aliphatic polyester polyol (A) was within the range of 0.5 to 10.
[0122] Next, the hot adhesive strength, seal strength, and hot water adhesive strength of the laminates of Example 5 and Comparative Example 2 were measured. For the measurements, the total ink coverage was 500% and 200%. The details of the measurement procedure are as follows.
[0123] [Measurement of adhesive strength after retort (120℃)] A three-sided bag was made using the laminate, and water was sealed in the three-sided bag. Then, a retort heat treatment (120°C x 30 minutes) was performed using a retort treatment device (manufactured by Hisaka Works, Ltd.). After the retort heat treatment, a laminate sample was taken by cutting into a width of 15 mm, and the interlayer strength between the ink layer and the layer in contact with the ink layer was measured. The measured peel strength is shown in the "120°C x 30 minutes" column in Table 3. Table 3 also shows the adhesive strength at room temperature before the heat treatment.
[0124] [Measurement of adhesive strength after retort (130℃)] A three-sided bag was made using the laminate, and water was sealed in the three-sided bag. Then, a retort heat treatment (130°C x 30 minutes) was performed using a retort treatment device (manufactured by Hisaka Works, Ltd.). After the retort heat treatment, a laminate sample was taken by cutting it into a width of 15 mm, and the interlayer strength between the electrostatic ink layer and the layer in contact with the electrostatic ink layer was measured. The measured peel strength is shown in the "130°C x 30 minutes" column in Table 3.
[0125] [Measurement of seal strength (before heat treatment)] A pair of laminates of Example 5 was heat-sealed under conditions of 180°C, 0.2 MPa, and 1 second, with the unstretched polypropylene films overlapping each other. This resulted in heat welding of the unstretched polypropylene films to each other, and a measurement sample having a width of 15 mm was prepared. The seal strength of the measurement sample prepared was measured in accordance with JIS K 7127:1999. The measurement was performed using a tensile tester under conditions of a peel angle of 90°, a tensile speed of 300 mm / min, and room temperature (20°C), to measure the peel strength between the heat seals. This peel strength was defined as the seal strength "before heat treatment". The measurement results were as shown in Table 3. A similar measurement sample was prepared using the laminate of Comparative Example 2, and the same measurement was performed. The measurement results were as shown in Table 3.
[0126] [Measurement of seal strength (after boiling)] The measurement sample prepared in the above "Measurement of seal strength (before heat treatment)" was heated in water at 100°C for 30 minutes. The seal strength was then measured using the same procedure as in the above "Measurement of seal strength (before heat treatment)". The measurement results are shown in the "After boiling" column in Table 3.
[0127] [Measurement of seal strength after retort (120℃)] The measurement samples prepared in the above "Measurement of seal strength (before heat treatment)" were subjected to retort heat treatment (120°C x 30 minutes). The peel strength was measured using a tensile tester in the same manner as in "Measurement of seal strength (without heat treatment)". The measurement results are shown in the "120°C x 30 minutes" column in Table 3.
[0128] [Measurement of seal strength after retort (130℃)] The measurement samples prepared in the above "Measurement of seal strength (before heat treatment)" were subjected to retort heat treatment (130°C x 30 minutes). The peel strength was measured using a tensile tester in the same manner as in "Measurement of seal strength (before heat treatment)". The measurement results are shown in the "130°C x 30 minutes" column in Table 3.
[0129] [Measurement of hot water adhesive strength] The laminate was cut to a width of 15 mm, and the layers at the edge were peeled off, and the laminate was immersed in hot water at 90° C. and the peel strength was measured using a tensile tester. That is, the peel angle was free and the tensile speed was 300 mm / min. This peel strength is shown in Table 3 as the hot water adhesion strength.
[0130] [Table 3]
[0131] As shown in Table 3, it was confirmed that the seal strength of Example 5 was superior to that of Comparative Example 2, regardless of whether heat treatment was performed or not. When the ink coverage rate was 500%, Example 5 in particular had a higher adhesive strength than Comparative Example 2. Furthermore, the seal strength of Example 5 was sufficiently high even after boiling, whereas the seal strength of Comparative Example 2 significantly decreased after boiling.
[0132] Example 8 [Preparation of adhesive composition and laminate] A polyethylene terephthalate film (PET film, thickness: 12 μm) was prepared as a first substrate. A water-based primer resin (a resin containing polyethyleneimine, manufactured by Michelman, product name: DP050) was applied to one side of the PET film to form a primer layer. The amount of water-based polyethyleneimine applied was 0.10 to 0.18 g / m 2 The coating was applied so that the result was as follows.
[0133] A predetermined printing was performed on the surface of the primer layer using a printer manufactured by HP Indigo (product name: Indigo 2000). As the electrostatic ink composition, an electrostatic ink composition (HP Indigo Electroink) containing a thermoplastic resin containing a copolymer of ethylene acrylic acid and ethylene methacrylic acid was used. As the colors of the electrostatic ink composition, white (W), yellow (Y), magenta (M), and cyan (C) were used. As the ink coverage, one with W200% and one with C100%+M100%+Y100%+W200% were prepared. In Table 4, the former is referred to as "ink coverage (1)" and the latter is referred to as "ink coverage (2)". In this way, two types of samples with different ink coverage of the electrostatic ink composition were prepared.
[0134] The same adhesive composition as in Example 5 was prepared. The adhesive composition prepared as described above was applied to the printed surface, on which the electrostatic ink composition had been printed, using a hand laminator to form an adhesive layer. The application amount of the adhesive composition was 4.0 g / m 2 It was decided.
[0135] As the second substrate, a substrate film having a nylon film and a non-oriented polypropylene film in this order was prepared. The substrate film was attached to the adhesive layer so that the adhesive layer and the nylon film were in contact with each other to obtain a laminate. The curing time (aging) was 40°C for 2 days.
[0136] The adhesive strength (room temperature), hot adhesive strength (120°C), seal strength (before heat treatment) and seal strength (after boiling) of the laminate thus obtained were measured in the same manner as described above. The measurement results are shown in Table 4.
[0137] (Examples 9 to 12) A laminate was produced in the same manner as in Example 8, except that the amount of polyisocyanate (B) used in preparing the adhesive composition was changed as shown in Table 4. The produced laminate was evaluated in the same manner as in Example 8. The evaluation results are shown in Table 4.
[0138] Comparative Example 3 A laminate was produced in the same manner as in Comparative Example 1, except that lamination of the printed surface on which the electrostatic ink composition was printed was performed using a hand laminator machine instead of using a dry laminator. The color and ink coverage of the electrostatic ink composition were as shown in Table 4. The produced laminate was evaluated in the same manner as in Example 8. The evaluation results are shown in Table 4.
[0139] [Table 4]
[0140] As shown in Table 4, it was confirmed that in each Example, high adhesive strength and seal strength were obtained even under high-temperature hot water treatment conditions. It was also confirmed that the hot adhesive strength (120°C) and seal strength (before heat treatment and after boiling) could be sufficiently increased by adjusting the blending ratio of polyisocyanate (B) to aliphatic polyester polyol (A). On the other hand, it was confirmed that in Comparative Example 3, which does not use epoxy compound (C), the adhesive strength and seal strength were significantly reduced when exposed to high-temperature hot water treatment conditions. In Examples 8 to 12, the molar ratio of isocyanate groups contained in polyisocyanate (B) to hydroxyl groups contained in aliphatic polyester polyol (A) was within the range of 0.5 to 10.
[0141] (Examples 13 to 17) An adhesive composition was prepared by blending an aliphatic polyester polyol (A1) (Takelac A525, manufactured by Mitsui Chemicals, Inc.), a polyisocyanate (B1) (Takenate A52, manufactured by Mitsui Chemicals, Inc.), and 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate as the epoxy compound (C). The blending ratios were as shown in Table 5. Except for using such an adhesive composition, laminates were produced and evaluated in the same manner as in Examples 8 to 12. The evaluation results were as shown in Table 5.
[0142] Comparative Example 4 An adhesive composition was prepared by blending an aliphatic polyester polyol (A1) (Takelac A525, manufactured by Mitsui Chemicals, Inc.) as a polyol, and a polyisocyanate (B1) (Takenate A52, manufactured by Mitsui Chemicals, Inc.). The blending ratio was as shown in Table 5. A laminate was produced and evaluated in the same manner as in Comparative Example 3, except that such an adhesive composition was used. The evaluation results were as shown in Table 5.
[0143] [Table 5]
[0144] As shown in Table 5, it was confirmed that high adhesive strength and seal strength were obtained in each Example even when the combination of aliphatic polyester polyol and polyisocyanate was changed. It was also confirmed that the hot adhesive strength (120°C) and seal strength (before heat treatment and after boiling) could be sufficiently increased by adjusting the blending ratio of polyisocyanate (B1) to aliphatic polyester polyol (A1). On the other hand, it was confirmed that in Comparative Example 4, which does not use epoxy compound (C), the adhesive strength and seal strength were significantly reduced when exposed to high-temperature hot water treatment conditions. In Examples 13 to 17, the molar ratio of isocyanate groups contained in polyisocyanate (B1) to hydroxyl groups contained in aliphatic polyester polyol (A1) was within the range of 0.5 to 10.
[0145] [Stability evaluation] (Example 18) The stability of the aliphatic polyester polyol (A), polyisocyanate (B), and epoxy compound (C) used in Example 7 when mixed was evaluated by the following procedure. First, the following two types of mixtures were prepared. Mixture A: Polyisocyanate (42.9% by mass) + epoxy compound (57.1% by mass) Mixture B: Aliphatic polyester polyol (76.1% by mass) + epoxy compound (23.9% by mass)
[0146] Polyisocyanate and epoxy compound were mixed and then stored at 50°C. The sample stored for one month was designated mixture a(1), and the sample stored for two months was designated mixture a(2). Aliphatic polyester polyol and epoxy compound were mixed and then stored at 50°C. The sample stored for one month was designated mixture b(1), and the sample stored for two months was designated mixture b(2).
[0147] Aliphatic polyester polyol (A) was added to mixture a(1) and mixture a(2), and immediately thereafter the mixture was placed in a dry atmosphere (silica gel) at 40°C. The time-dependent change (0 to 100 hours) in the amount of remaining NCO was then examined using FT-IR (transmission method). The results are shown in FIG. 4. The horizontal axis of FIG. 4 indicates the time that has elapsed since the addition of aliphatic polyester polyol (A), and the vertical axis indicates the NCO reduction rate, which is calculated as the NCO reaction rate, with the time immediately after mixing as the base (0).
[0148] Polyisocyanate (B) was added to mixture b(1) and mixture b(2) after storage, and immediately thereafter, the mixture was placed in a dry atmosphere (silica gel) at 40°C. The change over time (0 to 100 hours) of the remaining amount of NCO was then examined by FT-IR (transmission method). The results are shown in FIG. 4. The horizontal axis of FIG. 4 indicates the time elapsed since the addition of polyisocyanate (B). FIG. 4 also shows the results of a control in which the three components (A), (B), and (C) were simultaneously mixed and the amount of NCO remaining immediately after mixing was measured. In each mixture, the mixing ratio of the three components was 64.6 mass% for (A), 15.2 mass% for (B), and 20.2 mass% for (C).
[0149] From the results shown in FIG. 4, it was confirmed that the adhesive composition using mixture a suppressed the progress of the reaction during storage more than the adhesive composition using mixture b, and was able to sufficiently maintain the reactivity. The reactivity of mixture a(1) and mixture a(2) was equivalent to that of the adhesive composition immediately after the three components (A), (B), and (C) were mixed simultaneously. This confirmed that mixture a was able to maintain good reactivity even when stored for a long period of time.
[0150] (Example 19) Mixture a(1), mixture a(2), mixture b(1) and mixture b(2) were prepared in the same manner as in Example 18. The adhesive compositions obtained by adding aliphatic polyester polyol (A) to mixture a(1) and mixture a(2) were applied to a non-oriented polypropylene film (CPP film) at a rate of 5 g / m 2 A CPP film was applied to the film, and another CPP film was placed on top of the film to bond the two CPP films together. The film was then placed in a dry atmosphere (silica gel) at 40°C to examine the change in adhesive strength over time (0 to 50 hours). The adhesive strength was measured using the same procedure as in "Measurement of adhesive strength (room temperature)" in Example 1. The measurement results are shown in Figure 5. The horizontal axis of Figure 5 indicates the time elapsed after the addition of the aliphatic polyester polyol (A).
[0151] The change over time in the adhesive strength of the adhesive compositions obtained by adding polyisocyanate (B) to mixtures b(1) and b(2) was also measured in the same manner as mixtures a(1) and a(2). The measurement results are shown in FIG. 5. The horizontal axis of FIG. 5 indicates the time elapsed after the addition of polyisocyanate (B). As a control, FIG. 5 also shows the results of the adhesive strength measured by simultaneously mixing the three components (A), (B), and (C) and bonding CPP films together immediately after mixing. The blending ratios of (A), (B), and (C) were the same for all mixtures.
[0152] From the results shown in FIG. 5, it was confirmed that the adhesive composition obtained using mixture a can maintain a higher adhesive strength than the adhesive composition obtained using mixture b. The adhesive strength rise of the adhesive compositions using mixture a(1) and mixture a(2) was equivalent to that of the adhesive composition immediately after the three components (A), (B), and (C) were mixed simultaneously. This confirmed that mixture a can maintain good adhesiveness even when stored for a long period of time.
[0153] (Example 20) In the same manner as in Example 18, mixture a(1), mixture a(2), mixture b(1) and mixture b(2) were prepared. The pot life test of the adhesive composition obtained by adding aliphatic polyester polyol (A) to mixture a(1) and mixture a(2) was performed according to the following procedure. After adding aliphatic polyester polyol (A), the adhesive composition was immediately diluted with a solvent (ethyl acetate) so that the concentration of the adhesive composition became 30% by mass. The viscosity of this diluted solution (170 g) was examined over time using a B-type rotational viscometer (rotation speed: 60 rpm, rotor: No. 1). The measurement was performed under atmospheric pressure at 24°C. The measurement was continued while replenishing ethyl acetate at regular intervals. The measurement results were as shown in FIG. 6. The horizontal axis of FIG. 6 indicates the elapsed time from the start of the viscosity measurement.
[0154] The change over time in adhesive strength of the adhesive compositions obtained by adding polyisocyanate (B) to mixtures b(1) and b(2) was also measured in the same manner as mixtures a(1) and a(2). The measurement results are shown in FIG. 6. FIG. 6 also shows, as a control, the measurement results of an adhesive composition prepared by simultaneously mixing the three components (A), (B), and (C). The blending ratios of (A), (B), and (C) were the same for all mixtures.
[0155] 6, the pot life of the adhesive compositions obtained using mixture a and mixture b was equivalent to that of the adhesive composition obtained by simultaneously mixing the three components (A), (B), and (C). This confirmed that mixture a and mixture b could maintain good coatability even after long-term storage.
[0156] [Evaluation of dynamic viscoelasticity] Example 21 A solvent was added to the adhesive composition of Example 7 and Comparative Example 1 to adjust the non-volatile content to 40% by mass to obtain a mixture liquid. This mixture liquid was formed into a film of 200 μm thickness on a release paper using a doctor blade. After drying for 24 hours at room temperature and in a nitrogen atmosphere to remove the solvent, the film was cured at 60° C. for 6 days to prepare a cured film (film thickness: 40 to 50 μm). This was cut into a width of 5 mm to prepare a rectangular sample. The dynamic viscoelasticity of the rectangular sample was measured using a commercially available dynamic viscoelasticity measuring device (manufactured by IT Measurement and Control Co., Ltd., device name: DVA-200). The measurement was performed under the following conditions, with the temperature rising from -50° C. at a rate of 5° C. / min. Length between gauge lines: 2cm Width: 0.485cm Deformation mode: Tensile Static dynamic ratio: 1.4 Set distortion: 0.16% (>1.00×10 8 Pa) Measurement frequency: 10Hz
[0157] FIG. 7 is a graph showing the results of dynamic viscoelasticity measurement of the cured product obtained by curing the adhesive composition of Example 7. FIG. 8 is a graph showing the results of dynamic viscoelasticity measurement of the cured product obtained by curing the adhesive composition of Comparative Example 1. The glass transition temperature of the cured product of Comparative Example 1 was 29.3°C. On the other hand, the glass transition temperature of the cured product of Example 7 was 14.4°C. This shows that the inclusion of an epoxy compound improves the flexibility of the cured product at room temperature. It is believed that the adhesive composition of the present disclosure can improve adhesive strength not only by penetrating the electrostatic ink layer, but also by softening it and relieving the stress caused by lamination. [Industrial Applicability]
[0158] According to the present disclosure, it is possible to provide a laminate capable of maintaining a sufficiently high adhesive strength between layers even under high-temperature hot water treatment conditions, and a method for producing the same. It is also possible to provide a curing agent, an adhesive composition, a two-component adhesive, and a cured product that are useful for obtaining such a laminate. It is also possible to provide a packaging material having excellent sealing properties by using such a laminate. It is also possible to provide a package packaged with a packaging material having excellent sealing properties. [Explanation of symbols]
[0159] 10...first substrate, 20...second substrate, 30...adhesive layer, 40...primer layer, 50...electrostatic ink composition, 60, 62...packaging material, 100, 110...packaging bag, 101...sealed portion, 102...container portion, 120...opening means, 121...half-cut line, 124...easy-open processing portion, 200...packaging body, 300...laminate.
Claims
1. An adhesive composition for adhering a printing surface on which an electrostatic ink composition is printed, comprising: The composition contains a polyol, a polyisocyanate, and a bifunctional alicyclic epoxy compound having epoxy groups at both ends, a molar ratio of an epoxy group contained in the alicyclic epoxy compound to an isocyanate group contained in the polyisocyanate is 0.5 to 10; The adhesive composition, wherein the polyol and the polyisocyanate form a urethane bond, and the alicyclic epoxy compound, or the alicyclic epoxy compound and the polyisocyanate crosslink the electrostatic ink composition.
2. The amount of coating when adhering the printed surface is 1 to 10 g / m 2 2. The adhesive composition according to claim 1, wherein
3. The adhesive composition according to claim 1 or 2, wherein the electrostatic ink composition is printed on a primer layer composed of a polyethyleneimine resin.
4. The coating amount of the polyethyleneimine resin is 0.01 to 1.5 g / m 2 The adhesive composition according to claim 3 ,
5. 5. The adhesive composition according to claim 1, which has a glass transition temperature of 20° C. or lower as determined by dynamic viscoelasticity measurement after curing.
6. The adhesive composition according to any one of claims 1 to 5, wherein a molar ratio of an isocyanate group contained in the polyisocyanate to a hydroxyl group contained in the polyol is 0.5 to 10.
7. The adhesive composition according to any one of claims 1 to 6, comprising 3 to 25 parts by mass of the alicyclic epoxy compound per 100 parts by mass of the polyol.
8. The adhesive composition according to any one of claims 1 to 7, comprising 10 to 50 parts by mass of the polyisocyanate per 100 parts by mass of the polyol.
9. The adhesive composition according to any one of claims 1 to 8, wherein the polyol is an aliphatic polyester polyol.
10. The polyisocyanate includes a xylylene diisocyanate derivative, The adhesive composition according to any one of claims 1 to 9, wherein the content of the xylylene diisocyanate derivative relative to the entire polyisocyanate is 10 mass% or more.
11. The adhesive composition according to any one of claims 1 to 10, wherein the alicyclic epoxy compound has a molecular weight of 500 or less.
12. A curing agent for an adhesive that adheres a printing surface on which an electrostatic ink composition is printed, The composition contains a polyisocyanate and a bifunctional alicyclic epoxy compound having epoxy groups at both ends, a molar ratio of an epoxy group contained in the alicyclic epoxy compound to an isocyanate group contained in the polyisocyanate is 0.5 to 10; A curing agent, wherein the cycloaliphatic epoxy compound or the cycloaliphatic epoxy compound and the polyisocyanate crosslink the electrostatic ink composition.
13. The polyisocyanate includes a xylylene diisocyanate derivative, The curing agent according to claim 12, wherein the content of the xylylene diisocyanate derivative relative to the entire polyisocyanate is 10 mass% or more.
14. The curing agent according to claim 12 or 13, wherein the molecular weight of the epoxy compound is 500 or less.
15. A two-component adhesive for adhering a printing surface on which an electrostatic ink composition is printed, comprising: A first liquid containing a base material; A two-component adhesive comprising:
16. The two-component adhesive according to claim 15 , wherein the base agent contains a polyol.
17. The two-component adhesive according to claim 16, wherein a molar ratio of isocyanate groups contained in the polyisocyanate contained in the curing agent to hydroxyl groups contained in the polyol contained in the base agent is 0.5 to 10.
18. The two-component adhesive according to claim 16 or 17, wherein the polyol contained in the base agent is an aliphatic polyester polyol.
19. A cured product obtained by curing the adhesive composition according to any one of claims 1 to 11.
20. 20. The cured product according to claim 19, which has a glass transition temperature of 20°C or lower as determined by dynamic viscoelasticity measurement.
21. A laminate including a first substrate, an adhesive layer, and a second substrate in this order, an electrostatic ink layer formed of an electrostatic ink composition between at least one of the first substrate and the second substrate and the adhesive layer; The adhesive layer is composed of the cured product according to claim 19 or 20, A laminate, wherein the electrostatic ink composition is crosslinked by the alicyclic epoxy compound, or by the epoxy compound and the polyisocyanate.
22. 22. The laminate of claim 21, further comprising a primer layer between the first substrate and the electrostatic ink layer, the primer layer comprising polyethyleneimine.
23. A packaging material comprising the laminate according to claim 21 or 22.
24. A package comprising the packaging material according to claim 23 and an item to be packaged with the packaging material.
25. A step of printing an electrostatic ink composition on one side of a first substrate to obtain a printed surface; and adhering the printed surface and one surface of a second substrate side using the adhesive composition according to any one of claims 1 to 11, In the bonding step, the polyol and the polyisocyanate contained in the adhesive composition form a urethane bond, and the alicyclic epoxy compound, or the alicyclic epoxy compound and the polyisocyanate crosslink the electrostatic ink composition.
26. A step of printing an electrostatic ink composition on one side of a first substrate to obtain a printed surface; A step of preparing an adhesive composition by mixing the first liquid and the second liquid in the two-component adhesive according to any one of claims 15 to 18; and adhering the printed surface and one surface of a second substrate side using the adhesive composition, In the bonding step, a urethane bond is formed between the polyol contained in the adhesive composition and the polyisocyanate, and the alicyclic epoxy compound, or the alicyclic epoxy compound and the polyisocyanate, crosslink the electrostatic ink composition.
Citation Information
Patent Citations
Adhesive composition
JP1994025636A
Polyurethane adhesive composition
JP1995011225A
Laminate adhesive and usage thereof
JP2003113359A
Aqueous polyurethane adhesive for lamination
JP2004352905A
Adhesive for laminate
JP2017043693A